Customer DÄ±nÄ±ng ExperÄ±ence at Korean Themed Restaurant: an Enhanced ServÄ±ce BlueprÄ±nt Approach - Hermawan, Pri; Muhammad, Narendra Radi (Department of Management, Faculty of Economics and Business, Brawijaya University, 2017)
As competition between restaurants getting fiercer, restaurant owners need to be able to differentiate themselves with other restaurants to attract and retain more customers. Offering ethnic-themed foods and ambiance is regarded as one of strategy to differentiate between one restaurant and the others. At the heart of this strategy, restaurant owners are encouraged to offer authentic and distinct dining experience so that people are attracted and willing to revisit the restaurant. Customers perceive dining experience by recognizing the clues exposed during service delivery process or what usually called as service clues. This paper aims to explore how customers perceive about service clues and how it affects their dining experience at an ethnic-themed restaurant. This paper uses a qualitative approach and proposes an enhanced service blueprint to obtain deeper understanding about customer dining experience. The findings show the role of service clue in shaping up customer experience in an ethnic-themed restaurant. Each clue contributes differently in building customer dining experience.